Model Development and Implementation of Sharia-Based Online Shops to the Financial System in Indonesia - M Andika Hariz Hamdallah (International Journal of Integrative Sciences, 2023)
The e-commerce startup model that is widely used today as a whole is conventional, and not based on sharia, even though in Indonesia the majority are Muslim and there are also many Islamic banks in Indonesia, in addition to the digital era that has been added 4.0. In this case, a sharia-based e-commerce startup should already exist and be born and even develop in the State of Indonesia. This study examines the existing online shop startup model, which I then developed so that it became a sharia system with a more focus on buying and selling transactions, Islamic buying and selling pillars and other transactions related to the online shop itself. The subjects of this research that become benchmarks are, among others, Startup Online Shops (Tokopedia, Lazada, Shoppee) as a model for developing the online shop so that later it can complement all existing e-commerce, the two OJK, because OJK is a state institution that aims to protect all forms of financial transactions in Indonesia, the three Ministries of MSMEs, because startups are part of MSMEs so there is a need for licensing carried out through the MSME Ministry. The targeted output is the creation of an Online Shop or Startup that is based on Sharia and can open up new jobs in it, besides that other outputs can be published nationally in the form of an accredited National Journal